Effect of different short term synchronization protocols on estrus and fertility in non-pregnant ewes during the breeding season - DURSUN, Ş (Journal of the Hellenic Veterinary Medical Society, 2019)
The aim of this study was to investigate the efficacy of different short term synchronization protocols on estrus and pregnancy rates in merino ewes that had not become pregnant after at least three matings during the breeding season. Three different protocols were used as follows: Group I: Ewes (n=30) were inserted intravaginal progesterone sponge (florogestan asetate; 30 mg) for 6 days plus PGF2α (125 μg, i.m.) at the time of sponge removal, Group II: Ewes (40) were treated same as in group 1 plus eCG (250 IU, i.m.) at time of sponge removal, and Group III: Ewes (n=38) were only injected with PGF2α at the same time with the ewes in the other two groups. Estrus was detected by rams (n=4), 24 hours after PGF2α and ewes detected in estrus were mated. Ten rams were used for mating. Pregnancy was diagnosed 60 days after mating by ultrasonography. Estrus, conception and pregnancy rates were: for Group I 100%, 73.3% and 73.3%, for Group II 92.5%, 89.2% and 82.5% and for Group III 81.6%, 100% and 81%. In Group III, pregnancy loss after pregnancy diagnosis was significantly higher (35.4%) compared with the other groups (Group I: 13.6% and Group II: 15%).